2021
DOI: 10.1186/s40462-021-00298-y
|View full text |Cite
|
Sign up to set email alerts
|

A partial migrant relies upon a range-wide cue set but uses population-specific weighting for migratory timing

Abstract: Background Many birds species range over vast geographic regions and migrate seasonally between their breeding and overwintering sites. Deciding when to depart for migration is one of the most consequential life-history decisions an individual may make. However, it is still not fully understood which environmental cues are used to time the onset of migration and to what extent their relative importance differs across a range of migratory strategies. We focus on departure decisions of a songbird… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 91 publications
3
7
0
Order By: Relevance
“…In this study we 1) investigated the spring and autumn migratory strategies of Stone-curlews belonging to four Italian populations, two from the North and two from the center of the peninsula; 2) performed a preliminary evaluation of the possible role of exogenous factors in modulating the phenology of autumn migration. We expected a higher proportion of migrants in northern populations than in southern ones, as reported for other Palearctic migrants (Newton & Dale 1996, Newton 2008, Linek et al . 2021) and suggested for the Stone-curlew (Delany et al .…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…In this study we 1) investigated the spring and autumn migratory strategies of Stone-curlews belonging to four Italian populations, two from the North and two from the center of the peninsula; 2) performed a preliminary evaluation of the possible role of exogenous factors in modulating the phenology of autumn migration. We expected a higher proportion of migrants in northern populations than in southern ones, as reported for other Palearctic migrants (Newton & Dale 1996, Newton 2008, Linek et al . 2021) and suggested for the Stone-curlew (Delany et al .…”
Section: Introductionsupporting
confidence: 66%
“…2) performed a preliminary evaluation of the possible role of exogenous factors in modulating the phenology of autumn migration. We expected a higher proportion of migrants in northern populations than in southern ones, as reported for other Palearctic migrants (Newton & Dale 1996, Newton 2008, Linek et al 2021 and suggested for the Stone-curlew (Delany et al 2009, Biondi & Pietrelli 2015. Northern breeding birds should leave their wintering/breeding areas earlier than birds breeding more in the South as observed in other Palearctic species (Newton & Dale 1996, Newton 2008, Ambrosini et al 2016, Briedis et al 2020.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations